Taxing the Financially Integrated Multinational Firm - Niels Johannesen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2010)
This paper develops a theoretical model of corporate taxation in the presence of financially integrated multinational firms. Under the assumption that multinational firms at least partly use internal loans to finance foreign investment, we find that the optimal corporate tax rate is positive from the perspective of a small, open economy. This finding contrasts the standard result that the optimal source based capital tax is zero. Intuitively, to the extent that multinational firms finance investment in country i with loans from affiliates in country j, the burden of corporate taxes in the latter country partly fall on investment and thus workers in the former country. This tax exporting mechanism introduces a scope for corporate taxes, which is not present in standard models of international taxation. Accounting for the internal capital markets of multinational firms thus represents a way to resolve the tension between standard theory predicting zero capital taxes and the casual observation that countries tend to employ corporate taxes at fairly high rates.
Keywords: 330; Unternehmensbesteuerung; Multinationales Unternehmen; Kapitalmobilität; Optimale Besteuerung; Unternehmensfinanzierung; Theorie